An analysis of the transport properties and mechanical stability of rapidly solidified Al-Sb alloy (JOURNAL OF ADVANCES IN PHYSICS, 2015)
The structure of a series of AlSb alloys prepared by melt spinning have been studied in the as melt–spun ribbons as a function of antimony content .The stability of these structures has been related to that of the transport and mechanical properties of the alloy ribbons. Microstructural analysis was performed and it was found that only Al and AlSb phases formed for different composition. The electrical, thermal and the stability of the mechanical properties are related indirectly through the influence of the antimony content. The results are interpreted in terms of the phase change occurring to alloy system. Electrical resistivity, thermal conductivity, elastic moduli and the values of micro hardness are found to be more sensitive than the internal friction to the phase changes